(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to analyze the acquisition of a second language at the Muhammadiyah Bodon boarding school. This research was conducted because we wanted to know the second language acquisition of Muhammadiyah Bodon boarding school students in the form of word classes. The data source for this research is students’ second language acquisition in the form of a word class of eight students. The data for this research are students Muhammadiyah Bodon boarding school. The method used in this research is a descriptive method with a qualitative approach, namely describing the description of the form of second language acquisition in the form of word classes at the Muhammadiyah Bodon boarding school. The instruments in this research are documentation and observation by analyzing second language acquisition in the form of word classes mastered by students. The data analysis technique, namely data reduction, can be interpreted as reducing data. Next, the process of collecting information is arranged based on the groupings that have been made, then the researcher can draw conclusions. The results of this research indicate that students’ second language acquisition can be conveyed well because they are able to express second language acquisition in the form of word classes with proficient responses.